2022
DOI: 10.3389/fcell.2022.925457
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the sGC Stimulator BAY 41-2272 Binding Site on H-NOX Domain and Its Regulation by the Redox State of the Heme

Abstract: Soluble guanylate cyclase (sGC) is the main receptor of nitric oxide (NO) and by converting GTP to cGMP regulates numerous biological processes. The β1 subunit of the most abundant, α1β1 heterodimer, harbors an N-terminal domain called H-NOX, responsible for heme and NO binding and thus sGC activation. Dysfunction of the NO/sGC/cGMP axis is causally associated with pathological states such as heart failure and pulmonary hypertension. Enhancement of sGC enzymatic function can be effected by a class of drugs cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…2). These data, along with the other reports on bacterial H-NOX, strongly suggest that the Npun H-NOX protein domain is in the Fe(II) -H-NOX diamagnetic complex form (Boon et al, 2006;Tsai et al, 2012;Dai et al, 2012;Alexandropoulos et al, 2016;Makrynitsa et al, 2022).…”
Section: Protein Sample Preparationsupporting
confidence: 80%
See 1 more Smart Citation
“…2). These data, along with the other reports on bacterial H-NOX, strongly suggest that the Npun H-NOX protein domain is in the Fe(II) -H-NOX diamagnetic complex form (Boon et al, 2006;Tsai et al, 2012;Dai et al, 2012;Alexandropoulos et al, 2016;Makrynitsa et al, 2022).…”
Section: Protein Sample Preparationsupporting
confidence: 80%
“…The available structural studies by X-ray crystallography do not indicate significant changes between the various complexes of bacterial H-NOX domains, either in complexes with or without diatomic gases (practically all available models show significant similarity with RMSD < 0.3Å (Makrynitsa et al, 2019 ). Thus, NMR conformational and dynamic studies of other bacterial H-NOX domains are gaining interest indicating sites of interaction and other conformational modifications shedding light to analogous mechanisms of action in the human H-NOX domain (Makrynitsa et al 2022 , 2021 ; Argyriou et al, 2021 ; Erbil et al, 2009 ). Lately, structural studies have been reported regarding the NMR conformational data of Nostoc sp .…”
Section: Biological Contextmentioning
confidence: 99%
“…From a pharmacological perspective still many features of the sGCs binding site remain open: it is less well defined than that of sGCa (6,43); the molecular mechanism of its redox sensitivity amongst the many cysteines that have been mutated and analysed in sGC (6,39,(44)(45)(46)(47)(48)(49)(50) without leading to a clear pecking order with respect to redox regulation; why ODQ reduces the basal activity of sGC (21); and why the basal activity of purified apo-sGC is higher than that of sGC (51). The latter may be explained by our pilot experiment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The HCV-IRES stock concentration for the titration experiments was 5 mM, while the polyU10 stock concentration for the titration experiments was 2.5 mM. Chemical shift perturbation values were calculated using the following equation [39][40][41][42]:…”
Section: Titration Experimentsmentioning
confidence: 99%